Eating disorders among women of childbearing age - Bień, Agnieszka Maria; Pieczykolan, Agnieszka (Journal of Education, Health and Sport, 2017)
Introduction. Nutrition is one of the fundamental human needs, which allows for the proper functioning of the body. Nowadays, people are increasingly turning attention to the type and quantity of food intake, in order to preserve health and slim. Rigorous adherence to the principles of nutrition only healthy meals can lead to disorder orthorexia nervosa, which can lead to many complications (such as weight loss, vitamin deficiencies and mineral, hormonal disorders, psychological problems). The aim of the study was to investigate the prevalence of eating disorders such orthorexia nervosa in women of childbearing age and to check whether there is a relationship between the occurrence of eating disorders and a global orientation of life of respondents. Material and method. The study included 280 women aged between 18 and 35 years old who voluntarily joined the study. The study used the questionnaire technique, consisting of the author's questionnaire and standardized research tools (ORTO-15 Questionnaire, the SCOFF Eating Disorders Questionnaire and the Sense of Coherence Scale SOC-29). Results. After conducting these studies found an association between the occurrence of eating disorders such as orthorexia nervosa to religion, and between type of eating disorder anorexia and bulimia and marital status, and body mass index (BMI). It was also shown that the lower the overall level of sense of coherence and its components is more common in individuals at risk of developing anorexia or bulimia. Conclusion. There is a relationship between the occurrence of eating disorders such as orthorexia nervosa to religion. There is a relationship between the occurrence of eating disorders such as anorexia and bulimia marital status and body mass index of women.